Breeding for increased grain protein and micronutrient content in wheat: Ten years of the GPC-B1 gene. (January 2017) - Tabbita, Facundo; Pearce, Stephen; Barneix, Atilio J.
Abstract: To provide food and nutrition security for a growing world population, continued improvements in the yield and nutritional quality of agricultural crops will be required. Wheat is an important source of calories, protein and micronutrients and is thus a priority to breed for improvements in these traits. The GRAIN PROTEIN CONTENT-B1 ( GPC-B1 ) gene is a positive regulator of nutrient translocation which increases protein, iron and zinc concentration in the wheat grain. In the ten years since it was cloned, the impacts of GPC-B1 allelic variation on quality and yield traits have been extensively analyzed in diverse genetic backgrounds in field studies spanning forty environments and seven countries. In this review, we compile data from twenty-five studies to summarize the impact of GPC-B1 allelic variation on fifty different traits. Taken together, the results demonstrate that the functional copy of the GPC-B1 gene is associated with consistent positive effects on grain protein, Fe and Zn content with only marginally negative impacts on yield. We conclude that the GPC-B1 gene has the potential to increase nutritional and end use quality in a wide range of modern cultivars and environments and discuss the possibilities for its application in wheat breeding. Highlights: GPC-B1 positively impacts protein, Zn and Fe in wheat grain. The functional GPC-B1 allele is rare among modern cultivars. We provide a summary of GPC-B1 effects on yield and quality traits from 25 studies. GPC-B1 has positive effects on quality traits and negligible impacts on yield.